2017
DOI: 10.3389/fpls.2017.02023
|View full text |Cite
|
Sign up to set email alerts
|

RNA Editing Responses to Oxidative Stress between a Wild Abortive Type Male-Sterile Line and Its Maintainer Line

Abstract: RNA editing of mitochondrial gene transcripts plays a central role during plant development and evolutionary adaptation. RNA editing has previously been reported to differ between the rice cytoplasmic male sterile (CMS) line and its maintainer line, which has been suggested as a cause for their different performances under environmental stress. To specifically test this hypothesis, a wild abortive (WA) CMS line (Huhan-1A) and its maintainer line (Huhan-1B) were utilized to investigate performances in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In order to further explore the possible relationship between RNA editing and plant stress, we selected a total of six genes from chloroplasts and mitochondria to evaluate their expression, based on previous studies [27,38,39]. The RPS14 gene represented important chloroplast proteins, and the fluctuant editing efficiency and gene expression of RPS14 were associated with cytokinins against stress [39,40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further explore the possible relationship between RNA editing and plant stress, we selected a total of six genes from chloroplasts and mitochondria to evaluate their expression, based on previous studies [27,38,39]. The RPS14 gene represented important chloroplast proteins, and the fluctuant editing efficiency and gene expression of RPS14 were associated with cytokinins against stress [39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Under salt stress, PSBF and NDHB likely showed an elevated editing percentage, linked to PSII repair and increase in NDHB gene translation [39]. In rice, atp6 , atp9 , and ccmC were related to mitochondrial electron transport chain and had been selected to test RNA editing during stress exposure [38]. In our study, these reported genes in poplar were obtained from National Center for Biotechnology information and showed different expression owing to drought.…”
Section: Resultsmentioning
confidence: 99%
“…All rights reserved Chan, 2015;Choudhury et al, 2017;Farooq et al, 2019), which might in turn affect the redox status of TRXs and MORFs, and assembly of the editosome, eventually leading to changes in RNA editing efficiencies for an adaptive response. In support of this notion, a previous study in rice showed that mitochondria RNA editing was affected by oxidative stress (Xiong et al, 2017).…”
Section: Accepted Articlementioning
confidence: 78%
“…The culture solution, formulated as described by Chen et al [ 41 ], was replaced every two days. Following the procedure given by Xiong et al [ 42 ], ten-day old seedlings of uniform size were transferred into the same solution supplemented with 60 mM H 2 O 2 for two days, at which point the extent of necrotic and chlorotic damage was determined. The experiment consisted of three replicates, each involving 16 seedlings per line.…”
Section: Methodsmentioning
confidence: 99%